2011
DOI: 10.1063/1.3535579
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary games defined at the network mesoscale: The Public Goods game

Abstract: The evolutionary dynamics of the Public Goods game addresses the emergence of cooperation within groups of individuals. However, the Public Goods game on large populations of interconnected individuals has been usually modeled without any knowledge about their group structure. In this paper, by focusing on collaboration networks, we show that it is possible to include the mesoscopic information about the structure of the real groups by means of a bipartite graph. We compare the results with the projected (coau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
98
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 53 publications
1
98
0
Order By: Relevance
“…Therefore, the bipartite formulation allows to study, e.g., different types of probability densities for the number of connections of the agents and for the number of elements of the groups. In particular, in [19,20] it is shown that the use of realistic patterns of connections for agents and groups leads to an increase of the cooperation with respect of the aforementioned case of scale-free networks. In brief, the recent works on the evolutionary dynamics of the PGG (see [25] for a recent comprehensive review) have tried to explain the emergence of cooperation by incorporating the actual structure of group interactions relying on real data about social and collaboration networks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the bipartite formulation allows to study, e.g., different types of probability densities for the number of connections of the agents and for the number of elements of the groups. In particular, in [19,20] it is shown that the use of realistic patterns of connections for agents and groups leads to an increase of the cooperation with respect of the aforementioned case of scale-free networks. In brief, the recent works on the evolutionary dynamics of the PGG (see [25] for a recent comprehensive review) have tried to explain the emergence of cooperation by incorporating the actual structure of group interactions relying on real data about social and collaboration networks.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this assumption is somewhat unrealistic as it does not reflect the social structure of groups as revealed, for example, by real collaboration networks [22][23][24]. To incorporate the group structure into the formulation of the PGG in [19][20][21] the authors make use of bipartite graphs. In a bipartite graph there are two different types of nodes representing respectively, in the case of the PGG, agents and groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the seminal paper introducing games on grids [18], evolutionary games on graphs and complex networks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have proven instrumental in raising the awareness of the fact that relaxing the simplification of well-mixed interactions may lead to qualitatively different results that are due to pattern formation and intricate organization of the competing strategies, which reveals itself in most unexpected ways. Specifically for the spatial public goods game [38,39], it has recently been shown that inhomogeneous player activities [40], appropriate partner selection [41,42], diversity [43][44][45], the critical mass [46], heterogeneous wealth distributions [47], the introduction of punishment [48,49] and reward [50], as well as both the joker [51] and the Matthew effect [52], can all substantially promote the evolution of public cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…This representation reflects the interaction of nodes through multiple layers of links, which cannot be captured by the classical singlelayer network representation. This multiplex representation has long been considered by sociologists (multiplex tie [6][7][8], and although some results concerning multiplex networks' modeling and structure have been recently proposed, [9][10][11][12][13][14][15][16][17] the study of centrality parameters in such networks has not yet been addressed satisfactorily. The aim of this paper is to propose a definition of centrality in multiplex networks, and illustrate potential applications.…”
mentioning
confidence: 99%